Refusal: Verbs and Strategies. A Pragmatic Study - Ali, Sherzad S.; Othman, Ayad F. (Humanities Journal of University of Zakho, 2018)
The present research entitled “Refusal: Verbs and Strategies. A Pragmatic Study “this research deals with the principles and strategies of refusing within verbs of requesting, offering, invitation and suggestion. The research is divided into three levels of individuals of society. The levels are the same level, the high-low rank level and the low-high rank level. The ratio of each refusal strategy used is determined according to general descriptive analytical methodology depending on statistical data in analyzing each strategy ratio. The research consists of two chapters and introduction. The first one deals with refusal strategies while the second one deals with speech act of refusing. The research has come up with many findings with writing the abstract in Arabic and English.